A NEW LOOK AT THE PATHOGENESIS OF ADENOMYOSIS - M. M. Damirov; A. M. Shabanov (Неотложная медицинская помощь, 2016)
PURPOSE. Сomprehensive study of morphological features in patients with adenomyosis.MATERIAL AND METHODS. Comprehensive clinical and morphological study was performed in 40 adenomyosis patients who had been operated (the average age 44,1±3,47 years) with histologically verified diagnosis. A comprehensive morphological study using survey, histochemical and morphometric methods was carried out.RESULTS. Growth of heterotopic lesions was accompanied by a marked plethora microvasculature of the myometrium, lymphostasis, oedema of the tissues of the myometrium, number of tissue basophils increase around the endometriosis, alcian-positive glycosaminoglycans high content in the intercellular substance. Local changes taking place in the uterus play important role in adenomyosis occurrence. The research results allow to consider the onset and progression of adenomyosis from the position of the concept of the local failure of the uterus connective tissue. Knowledge of the morphological basis of adenomyosis allows to diagnose the pathology better and to interpret the results obtained by the application of additional methods of examination .